PERBEDAAN HASIL BELAJAR EKONOMI DENGAN MENGGUNAKAN METODE PETA KONSEP DAN METODE CERAMAH PADA SISWA KELAS X SMA NEGERI 16 PADANG - Fera, Mutia; Tanjung, Mirna; Jolianis, Jolianis (Pendidikan Ekonomi, 2013)
ABSTRACTÂ The aim of research was to know the differentiation of studentsâ studying result between the concept map method and the lecturing method to the X grade students of SMA Negeri 16 Padang.The type of this research was an experimental research. The population of the research was all of X grade students in SMA Negeri 16 Padang which was calculated 292 students, the sample of this research was only 73 students which was taken by using analysis technique was the Z test, before the test was given, the test was firstly tested and then the result of the was analyzed by using reability analysis, the level of difficulty and the differentiate capacity of the test. After that, to test the differentiation of studentsâ result, the writer used Z test with a = 0,05.The data analysis from the average result of the studentsâ posstest in experimental class was 81,28 with the deviation standard of 6,95 while the average posstest result for control class was 76,46 with deviation standard 5,46. from the result of hipothesis test the Z calculated = 3,29 and Z tabel = 1,96 means that Z calculated > Z tabel so that the alternative hypotesis could be accepted. It means that there were significant differentiation between studentsâ economic results in both experimental and control class, where the experimental class got a higher result than the control class. In this case, the differentiation was believed as the effect of the action which is given to the experimental class which was the learning process by using concept map method. To increase the studentsâ result in studying economics especially for X grade students of SMA Negeri 16 Padang, it is suggested to the economics teachers to consider the use of concept map method beside the lecturing method.